2015
DOI: 10.1152/ajprenal.00203.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction confers albumin-induced NLRP3 inflammasome activation and renal tubular injury

Abstract: . Mitochondrial dysfunction confers albumin-induced NLRP3 inflammasome activation and renal tubular injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 23 publications
3
57
0
3
Order By: Relevance
“…They further investigated the mechanism and found that the endocytosis of ultrafiltered albumin in tubules might induce endoplasmic reticulum stress, which plays an important role in NLRP3 inflammasome activation. Meanwhile, our study showed that the NLRP3 inflammasome/caspase-1/mitochondria axis mediated the mouse proximal tubular cell defect [32], which might be the mechanism of the mouse proximal tubular cell tight junction injury by albumin [33]. In albumin-overloaded mice, we observed severe tubular structure damage, cell apoptosis and epithelial cell phenotype transition, as well as mitochondrial dysfunction.…”
Section: Inflammasome and Chronic Kidney Diseasementioning
confidence: 99%
“…They further investigated the mechanism and found that the endocytosis of ultrafiltered albumin in tubules might induce endoplasmic reticulum stress, which plays an important role in NLRP3 inflammasome activation. Meanwhile, our study showed that the NLRP3 inflammasome/caspase-1/mitochondria axis mediated the mouse proximal tubular cell defect [32], which might be the mechanism of the mouse proximal tubular cell tight junction injury by albumin [33]. In albumin-overloaded mice, we observed severe tubular structure damage, cell apoptosis and epithelial cell phenotype transition, as well as mitochondrial dysfunction.…”
Section: Inflammasome and Chronic Kidney Diseasementioning
confidence: 99%
“…Based on a previous study [12], we investigated the effects of SS-31 on the change in mtDNA copy number, ATP synthases, and the release of cytosolic Cyt C three days post-injury to analyze mitochondrial dysfunction. SCI induced significant abnormalities in mitochondrial function, as shown by the reduction in mtDNA copy number (1.0 ± 0.12, P=0.007, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mitochondria are a major source of reactive oxygen species (ROS) and contribute to cell signal transduction [12]. Mitochondrial dysfunction leads to an increase in ROS production, mitochondrial DNA damage (copy number reduction and mutation), disorders in oxidative phosphorylation of the mitochondrial respiratory chain, and the reduction of ATP production [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations